(untitled) (Biological Sciences - PJSIR, 1995)
The graft copolymerization of polymethylmeth-acrylate onto casein has been investigated using potassium persulfate initiator inaqueous medium. The effectsof monomer. backbone and ascorbic acid (asactivator) have been discussed inthe lightof percent grafting (GR), grafting efficiency(GE)and ratesofRg, Rp, Rh.The proof of grafting has also been established.